Initial immune response after exposure to Mycobacterium tuberculosis or to SARS-COV-2: similarities and differences - Aiello, Alessandra; Najafi-Fard, Saeid; Goletti, Delia (Frontiers in Immunology, 2023)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) and Coronavirus disease-2019 (COVID-19), whose etiologic agent is severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), are currently the two deadliest infectious diseases in humans, which together have caused about more than 11 million deaths worldwide in the past 3 years. TB and COVID-19 share several aspects including the droplet- and aerosol-borne transmissibility, the lungs as primary target, some symptoms, and diagnostic tools. However, these two infectious diseases differ in other aspects as their incubation period, immune cells involved, persistence and the immunopathological response. In this review, we highlight the similarities and differences between TB and COVID-19 focusing on the innate and adaptive immune response induced after the exposure to Mtb and SARS-CoV-2 and the pathological pathways linking the two infections. Moreover, we provide a brief overview of the immune response in case of TB-COVID-19 co-infection highlighting the similarities and differences of each individual infection. A comprehensive understanding of the immune response involved in TB and COVID-19 is of utmost importance for the design of effective therapeutic strategies and vaccines for both diseases.